Pengaruh Tayangan Film Religi terhadap Akhlak Siswa: Studi di SMK Negeri Cikarang Barat - Robi’ah Al-Adawiyah; Rabiyanur Lubis (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2015)
Impressions flourishing religious film that is both entertaining as well in addition to providing moral values are positive. Because the stories shown that about how religious people in the act, behave and speak the word, both in the human relationship with God, parents, relatives, friends, neighbors, even to animals, plants, and inanimate objects. The problems of this study is,